Effectiveness of Interactive Reading Materials on the Reading Performance in Filipino of Grade Three Pupils - Aguinaldo, Agot (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of interactive reading materials on the reading performance in Filipino of Grade Three pupils at Mayamot Elementary School during the School Year 2025–2026. Employing an experimental research design with a parallel group approach, the study involved 60 pupils divided equally into experimental and control groups. The experimental group was exposed to interactive reading materials, while the control group received traditional instruction. Pretest and posttest assessments were administered to measure reading performance.Findings revealed that both groups demonstrated improvement from pretest to posttest, with performance levels increasing from fairly satisfactory to satisfactory. Statistical analysis showed significant differences within each group’s pretest and posttest scores, indicating that both instructional approaches contributed to improved reading performance. However, no significant difference was found between the posttest results of the experimental and control groups, suggesting that interactive reading materials were comparable in effectiveness to traditional teaching methods. Moreover, variables such as sex, sibling position, family size, monthly family income, parents’ educational attainment, and occupation did not significantly influence pupils’ reading performance.The study concluded that while interactive reading materials are effective in enhancing reading performance, traditional teaching methods also yield similar improvements. Thus, the integration of interactive materials can serve as a supplementary strategy rather than a sole instructional approach. It is recommended that teachers incorporate varied and engaging reading materials to enrich pupils’ learning experiences. Additionally, further studies may explore other variables and contexts to validate and extend the findings.